logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Ad
Home  >>  CBSE XII  >>  Math
0 votes

Prove that : \[ 2tan^{-1} \bigg( \frac{1}{2} \bigg) + tan^{-1} \bigg( \frac{1}{7} \bigg) = tan^{-1} \bigg( \frac{31}{17} \bigg) \]

Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • \( 2tan^{-1}x=tan^{-1}\frac{2x}{1-x^2}\)
  • \( tan^{-1}x+tan^{-1}y=tan^{-1}\frac{x+y}{1-xy}, xy <1\)
L.H.S \( tan^{-1}\frac{4}{3}=tan^{-1}\frac{1}{7}\)
\( = tan^{-1}\frac{\frac{4}{3}=\frac{1}{7}}{1-\frac{4}{21}}=tan^{-1}\frac{31}{17}\) = R.H.S
answered Feb 28, 2013 by thanvigandhi_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...